PEMISAHAN DAN IDENTIFIKASI EKSTRAK KASAR SESKUITERPEN DAUN BUNGA MATAHARI (Helianyhus annuus L.) DENGAN KROMATOGRAFI LAPIS TIPIS - Muti'ah, Roihatul; Hayati, Elok Kamilah; Triastutik, Yani (ALCHEMY, 2013)
The purpose of this research wasto separate and identify the leaf crude extracts esquiterpene of Sun flower (Helianthus annuus L.) using thin layer chromatography.Sun flower leaf maceration method performed with the solvent methanol. Then performed liquid extraction with ethyl acetate and n-hexane solvent. Ethyl acetate extract fraction and n-hexane extract fraction furth erphyto chemical test. After being test edphyto chemical with reagents, both extracts was followed by sesquiterpene content identification using thin layer chromatography (TLC)Â  analytic.Phytochemical test result from ethyl acetate extract fraction was positive terpenoid, sesquiterpene and triterpene, while n-hexane extractfraction positive terpenoid, sesquiterpene andsteroid. All egedsesquiterpene with eluentdichloromethane: ethyl acetate (4,8:0,2) is shown with apurplestain. In the ethyl acetate extract fraction all egedsesquiterpene having Rf values of 0.89; 0.94, and 0.96. While n-hexane extract fraction, the resulting eluental legedsesquiterpene Rf 0.49; 0.8,and 0.99.